Chemical Analysis of Barley Under Different Irrigation and Fertilizing Systems - Maleki Farahani, S.; Chaichi, M.R.; Mazaheri, D.; Tavakkol Afshari, R.; Savaghebi, G. (Asian Journal of Chemistry, 2010)
The effect of different fertilizing systems and drought stress during grain development on grain minerals of barley (Hordeum vulgare L.) was studied in field experiments on a clay-loamy soil during 2007 growing season. The treatments consisted of three irrigation regimes (main plots) of: non-stressed (NS, normal irrigation until the end of the plant physiological maturity), medium stress (MS, ceased irrigation from the beginning of flowering to the initiation of seed filling stage and severe stress (SS, ceased irrigation from the initiation of flowering stage to the end of the physiological maturity) and 6 fertilizing systems consisted of no fertilizing (NF), phosphorous and nitrogen biofertilizers (BF), 100 % chemical fertilizer (NPK) (CF), vermicompost (VC) 5 t/ha, 50 % chemical fertilizer (NPK) + 50 % vermicompost (2.5 t/ha) (CV) and 50 % chemical fertilizer (NPK) + biofertilizer (CB), assigned to the sub plots. Drought stress significantly increased grain minerals of N, P, Zn and Mn by 12 %, 4 %, 27 % and 7 % compared to control (NS), respectively. Average nitrogen content of barley grain in chemical fertilizer (CF) was significantly more than the other treatments followed by integrated fertilizing systems (CB and CV). The P content of barley grain produced in BF fertilizer was significantly higher than other treatments. Iron and zinc content of barley grain increased by vermicompost application. However, Mn content of barley grain was higher in fertilized with chemical fertilizer.